Literature and feminism : an introduction - Morris, Pam (Blackwell, 1993)
This introduction to feminist literary criticism and theory assumes no previous knowledge of the field. It provides a guide to one of the most important, but also most difficult, areas of contemporary literary studies. Beginning with broad definitions of both "feminism" and "literature", the book then sets out (in Part One) the key terms, concepts and approaches distinctive to feminist literary criticism. Having developed this framework of ideas, the author next introduces the reader (in Part Two) to more complicated areas of theory and debate, and to the work of such thinkers as Cixous, Irigaray, Lacan and Kristeva. In addition to description and analysis, each chapter also contains structured exercises, a summary of the main points of the chapter and a guide to further reading. The text is illustrated throughout with excerpts from poetry, prose, fiction and critical works, many of which form the basis for close readings using the approaches and techniques described. The author also provides a glossary to terms used in the book. This book should be of interest to students and teachers of feminist literary criticism and theory.